Efektivitas Dalam Kurikulum Merdeka Dan Peranan Pengajar Untuk Para Pelajar - Rakha Rif'at Aryaputra; Hindun Hindun (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The independent curriculum is the newest educational curriculum in Indonesia and is currently being implemented by implementing freedom of learning for teachers and students. This independent curriculum is packaged to suit the needs of students, apart from that it also supports learning that is literate with the times. Apart from the educational curriculum, the role of the teacher is also very important for the success of learning in the classroom. This research uses a descriptive qualitative method that describes and analyzes the data that has been found in narrative form. This research does not describe data variables in the form of numbers, but this research places more emphasis on describing the phenomena or problems in this research. The technique for collecting this data uses note taking by reading references which are used as reference sources in this research. This data collection technique is also assisted by literature study as a reinforcement of the data that has been found by the author. Meanwhile, the data analysis technique goes through several stages, namely collecting data by adjusting the data grouping, then presenting the data in the form of a narrative or description, and finally drawing conclusions from the data that has been found and then analyzing it as well.